Shear Behaviour of RC T-Beams with Externally Bonded Discrete CFF Strips – A Experimental and Finite Element Study - Jaganathan, Jayaprakash; Abdul Samad, Abdul Aziz; M. Y, Mustafasanie; M.P, Anwar; Mohamed, Abdullahi Ali (International Journal of Sustainable Construction Engineering and Technology, 2014)
The application of fibre reinforced polymer (FRP) composites for retrofitting and strengthening of existing reinforced concrete (RC) structures has fascinated the attention of researchers and engineers in the recent decades. This paper presents the results of experimental and finite element (FE) investigation of shear behaviour of reinforced concrete T-beams repaired with externally bonded bi-directional discrete carbon fibre fabric (CFF) strips. The reinforced concrete T-beams were tested under four point bending system to investigate the performance of CFF shear strengthening scheme in terms of ultimate load carrying capacity. These beams were modelled using LUSAS software. To evaluate the behaviour of the simulated models, the predicted results were compared with the experimental results. The experimental results show that the gain in shear capacity of the CFF repaired beams ranged between 20% and 40% over the control beam. Thus, it can be concluded that the externally bonded CFF strips significantly increased the shear capacity of CFF repaired beams. It was generally observed that the developed FE model shows better agreement with the experimental results. The results of load-deflection profile, cracking pattern, modes of failure, and strain distribution in discrete CFF strips are presented.